Mediating Role of Health Promoting Behaviors on the Relationship between Self-Efficacy and Mental Health in Adolescent - Nafise Majidi Yaychi; Ramazan Hasanzade; Mahbobe Farmarzi; Alireza Homayoni (Hamadan University of Medical Sciences, 2019)
Aim: The role of self-efficacy in the life of individuals has been identified as an important factor in the emergence and maintenance of symptoms and health promotion behaviors. Therefore, considering that today mental health plays a fundamental role in the personality evolution, this study aimed to modeling the relationship between self-efficacy and the mediating of health promotion behaviors in students. Materials and Methods: This descriptive-correlational study was carried out on 260 people, who were the students in the secondary level of middle school in Sari city in the period of 1396-1397. The subjects were selected by multi-stage cluster sampling method. Data were collected by Sherer self-efficacy questionnaire, mental health scale, and Pender's health promotion behaviors questionnaire. Data were analyzed by SPSS 24 and Amos 23 software using the Pearson correlation coefficient and structural equation modeling. Findings: Based on the results there was a significant relationship between all variables of the research (p= 0.01). Based on investigating the indexes of the goodness of fit, the model has good fitness. Self-efficacy ways and health promotion behaviors have a direct and significant effect on the mental health, as well as, self-efficacy with mediating of health-promoting behaviors has an in direct and significant effect on the mental health (p<0.05). Based on the final model, self-efficacy with mediating of health-promoting behaviors has an indirect effect on mental health (R2= 0.06). Conclusion: Self-efficacy directly and through the mediation of health promotion behaviors is effective on the mental health of students.